Ecological irrigated land mapping: A review of papers from the Scopus database published in English for the period of last 20 years - Oymatov Rustam; Mamatov Dilshod; Aminova Guljahon; Khudoyberdiev Feruz (E3S Web of Conferences, 2024)
In scientific research, review articles or literature reviews are essential. Despite the abundance of resources on literature reviews, most of them only address the theoretical underpinnings of the protocols, nomenclatures, and review processes. Due to overlapping similarities, this may result in reporting that is not economical and may also generate confusion. We adopt a practical approach to describe and clarify the academic practice of conducting literature reviews in order to solve these limitations. The types, goals, factors, techniques, and contributions of literature reviews as stand-alone investigations are the main topics of our attention. Therefore, without becoming bogged down in the nuances of review protocols, procedures, and nomenclatures, our essay offers an overview that academics can rely on to navigate the important components of literature reviews as stand-alone and independent studies.